THE EFFECT OF CONVERGENT-DIVERGENT NOZZLE PROFILE ON ITS PERFORMANCE (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
The paper presents the effect of convergent-divergent nozzles profile across specified inlet pressures values from (1.5 bar-4 bar), with constant back pressure of (1 bar). The flow of air through three convergent-divergent nozzles was studied theoretically. The flow was assumed to be one-dimensional, adiabatic and reversible (isentropic). The flow parameters like static pressure ratio and Mach number were analyzed. The flow parameters were obtained in term of area ratio along the nozzle. MATLAB code was built in order to find the Mach number along the nozzles, by using Newton-Raphson method. The shockwave position inside the nozzles was determined, using "analytic method". ANSYS fluent 18 was used to simulate the flow through the three nozzles. Two- dimensional, turbulent and viscous models were utilized to solve the governing equations. K-? model was used to model the turbulent effect. The results concluded that, reduction in inlet pressure can not affect the flow upstream the throat. Also the shockwave appearance can be noticed by a sudden rise in static pressure associated with a sharp decrease in Mach number. Shockwave moves toward the throat by reduction the inlet total pressure .By comparison the static pressure distribution along the three nozzles where can be deduced that the profile has an effect on the flow character i.e. (static pressure Mach no).The best performance among the nozzles is the performance of nozzle (N1), which (75%) of its length work as nozzle at the lowest inlet pressure of (1.5bar) while (44% and 60%) of the nozzles length for (N2 and N3) respectively work as the nozzle.